2021
DOI: 10.1007/s00520-021-06290-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and acceptance of telemedicine among medical oncologists before and during the COVID-19 pandemic in Turkey

Abstract: Background As a result of technological developments in healthcare services, telemedicine is becoming widespread. We aimed to determine the effect of COVID-19 on Turkish medical oncologists’ opinions of telemedicine through a survey. Methods This study was conducted using an online questionnaire linked to an invitation e-mail sent to the members of the Turkish Medical Oncology Association mailing group between May and July 2020. Results Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent literature highlights the importance of telemedicine and telediagnosis wherever possible. Recent studies (Sahin et al, 2021) have shown that telemedicine was highly valued by oncologists during the Covid 19 pandemic in Turkey, particularly the "stored and forward' method most commonly used in telediagnosis, which is also presented here.…”
Section: Discussionmentioning
confidence: 93%
“…Recent literature highlights the importance of telemedicine and telediagnosis wherever possible. Recent studies (Sahin et al, 2021) have shown that telemedicine was highly valued by oncologists during the Covid 19 pandemic in Turkey, particularly the "stored and forward' method most commonly used in telediagnosis, which is also presented here.…”
Section: Discussionmentioning
confidence: 93%
“…Focusing on the eHealth adoption in recent times, the majority of the participants stated that they adopted either out of necessity or because there was no other alternative, clearly reflecting the impact of the COVID-19 pandemic on the surge in eHealth adoption in Saudi Arabia. Accordingly, studies in different countries [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] reflected an increased adoption of eHealth technologies, especially mHealth applications, for consultation, appointment booking, medicine orders, remote monitoring of chronic conditions such as diabetes, etc. However, research identifying the intention to use eHealth technologies in post-COVID-19 times in various countries is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…As further support for this statement, performance expectancy had no impact on the intention to use eHealth in a study conducted in Turkey [ 13 ]. Furthermore, all stakeholders, including physicians [ 14 , 15 ], patients, and especially older adults [ 16 , 17 , 18 ], reflected an increased use of eHealth applications in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…As a third limitation, the acceptance by patients and providers is another unknown in the application of such technologies. During the COVID-19 pandemic, the use of telecare has been well accepted by both the clinicians and the patients in Turkey [26], [51]. For our data calculations, we made assumptions of secondary visits to be performed over video platforms and supported this assumption by the expert cardio-vascular specialists, however the acceptance among patients is not clear.…”
Section: Limitationsmentioning
confidence: 99%
“…In the case of Turkey, telemedicine acceptance was fast during the Covid pandemic, yet for any new system to be successful it requires the capacity for expansion, financing, policies, governance, and partnership [26], [27]. The hypothetical benefits of adopting telemedicine presented in this work could inform and motivate future policies in this space.…”
Section: Introductionmentioning
confidence: 99%